Effects of preterm birth and ventilation on glomerular capillary growth in the neonatal lamb kidney. Issue 10 (October 2016) - Sutherland, Megan R.; Ryan, Danica; Dahl, Mar Janna; Albertine, Kurt H.; Black, Mary Jane
Abstract : Objectives: Preterm birth is linked to the development of hypertension later in life. This may relate to impaired glomerular capillary growth following preterm birth. The aim of this study was to determine the effects of preterm birth, and/or ventilation, on glomerular capillary growth in the neonatal lamb kidney. Methods: Four experimental groups were analysed: preterm lambs delivered at 130 days gestation (term = 147 days) and mechanically ventilated for 3 days (preterm ventilated: n  = 9), 133 days gestational controls (gestational control: n  = 5), term controls, unassisted breathing for 3 days (term control: n  = 8), and term lambs ventilated for 3 days (term ventilated: n  = 5). In perfusion-fixed kidneys, total nephron number, average total capillary length, and surface area per renal corpuscle were stereologically assessed, and total renal filtration surface area (TRFSA) was calculated. Results: In comparison with term controls, preterm lambs had significantly reduced glomerular capillary length, surface area, and TRFSA, indicative of a low renal functional capacity. Term-ventilated lambs exhibited significantly reduced glomerular capillary length and surface area compared with term controls, indicating that ventilation impairs glomerular capillary growth independently of preterm birth. Conclusion: Impaired glomerular capillary growth and subsequent reduced TRFSA following preterm birth may mediate the increased predisposition to hypertension later in life.